What is AI Literacy for Healthcare Professionals? A Foundational Competency for the Digital Health Era - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into clinical practice is rapidly transforming healthcare delivery, promising advancements in diagnostics, trea...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care